Penyakit Infeksi Saluran Napas Pneumonia Pada Balita, Orang Dewasa, dan Usia Lanjut - Misnadiarly (Pustaka Populer Obor, 2008)
Penyakit Infeksi Saluran Napas Pneumonia Pada Balita, Orang Dewasa, dan Usia Lanjut